Imprinted survival genes preclude loss of heterozygosity of chromosome 7 in cancer cells. Issue 1 (September 2016) - Boot, Arnoud; Oosting, Jan; de Miranda, Noel FCC; Zhang, Yinghui; Corver, Willem E; van de Water, Bob; Morreau, Hans; van Wezel, Tom
Abstract: The genomes of a wide range of cancers, including colon, breast, and thyroid cancers, frequently show copy number gains of chromosome 7 and rarely show loss of heterozygosity. The molecular basis for this phenomenon is unknown. Strikingly, oncocytic follicular thyroid carcinomas can display an extreme genomic profile, with homozygosity of all chromosomes except for chromosome 7. The observation that homozygosity of chromosome 7 is never observed suggests that retention of heterozygosity is essential for cells. We hypothesized that cell survival genes are genetically imprinted on either of two copies of chromosome 7, which thwarts loss of heterozygosity at this chromosome in cancer cells. By employing a DNA methylation screen and gene expression analysis, we identified six imprinted genes that force retention of heterozygosity on chromosome 7. Subsequent knockdown of gene expression showed that CALCR, COPG2, GRB10, KLF14, MEST, and PEG10 were essential for cancer cell survival, resulting in reduced cell proliferation, G1 ‐phase arrest, and increased apoptosis. We propose that imprinted cell survival genes provide a genetic basis for retention of chromosome 7 heterozygosity in cancer cells. The monoallelically expressed cell survival genes identified in this study, and the cellular pathways that they are involved in, offer new therapeutic targets for the treatment of tumours showing retention of heterozygosity on chromosome 7. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.